Identidade e discursivização em The Hobbit de J.R.R. Tolkien - Quesada, Vinícius Carvalho (2016)
Abstract: This study aims to understand how it happens the composition of the hero in The Hobbit novel J.R.R. Tolkien, by the bias of the French Semiotics theory, initiated by Greimas and the Group of semio-Linguistic Research School for Advanced Studies in Social Sciences, in the 1960s. Given the need to address an object of study with the most recent advances in theory, we seek to consider the discursive level in its nuances and determine how the figurative and thematic paths are constructed; towards this end, we use, in addition to the theory assumptions, we used the studies developed by Denis Bertrand in Caminhos da Semiótica Literária. With the volume of support directed to literary studies, we also address the role and relevance of the narrator in the novel we set out to analyze. We sought also authors like Fontanille and Zilberberg who, especially in their Tensão e Significação volume bring highly relevant information to contemplate the establishment of a hero and his constitution. Mixture and screening concepts are of fundamental importance in this work, for they are the basis for us to understand the way interactantial relations constitute the narrative level, beyond the way is the intertwining of forms over the determinants doings in the constitution of maturity of the hero. In a final moment, we seek to describe elements relating to the fundamental opposition which sustains all the construction of meaning in The Hobbit, as the elements seen throughout the generative route of sense of the novel associated in two poles and converge to the layers of the upper level of discourse. At that time, we seek to determine what the syntax and semantics are in The Hobbit, which sustain all narrative and all discursivization that, when building the route for creating a hero, contemplates as very significant prospect to the Gremasian Semiotics Theory: seeking to reveal doing (and the being) of the human in the world.